Cultura política e comportamento eleitoral no município de Frederico Westphalen/RS - Fritzen, Denise (2014)
This work aims to analyze cultural issues and democratic processes as well as the perceptions and the ideological behaviors from the political agents in Frederico Westphalen city in the state of Rio Grande do Sul. The research reveals the importance of political culture as an analytical variable of the political behavior of the citizens and shows as an important social reality dimension, as being central to the analysis performed on the gaúcho city. Starting from an analytical perspective which revolts the cultural issues and the democratic processes, as well as the perceptions and the ideological behavior from the political agents of the city, it starts from the idea of political culture as a key element in several historical contexts. The research aims to delineate parameters between electoral behavior of the citizens on the decision taking from strong personalist character and the theoretical aspects that govern the political culture, these ones as determinants in the electoral process of the city. The purpose is so to contribute the debate about the relation between the citizens`behavior in the possession of their political rights, the vote abandonment based on the party program, the strengthening of the democratic consolidation basis and the existing cultural influences.